GRP78 Mediates Cell Growth and Invasiveness in Endometrial Cancer. Issue 10 (October 2014) - Calì, Gaetano; Insabato, Luigi; Conza, Domenico; Bifulco, Giuseppe; Parrillo, Luca; Mirra, Paola; Fiory, Francesca; Miele, Claudia; Raciti, Gregory Alexander; Di Jeso, Bruno; Terrazzano, Giuseppe; Beguinot, Francesco; et al.
Abstract Recent studies have indicated that endoplasmic reticulum stress, the unfolded protein response activation and altered GRP78 expression can play an important role in a variety of tumors development and progression. Very recently we reported for the first time that GRP78 is increased in endometrial tumors. However, whether GRP78 could play a role in the growth and/or invasiveness of endometrial cancer cells is still unknown. Here we report that the silencing of GRP78 expression affects both cell growth and invasiveness of Ishikawa and AN3CA cells, analyzed by the (3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide) and transwell migration assay, respectively. At variance with Ishikawa cells, AN3CA cells showed, besides an endoplasmic reticulum, also a plasma membrane GRP78 localization, evidenced by both immunofluorescence and cell membrane biotinylation experiments. Intriguingly, flow cytometry experiments showed that the treatment with a specific antibody targeting GRP78 C‐terminal domain caused apoptosis in AN3CA but not in Ishikawa cells. Induction of apoptosis in AN3CA cells was not mediated by the p53 pathway activation but was rather associated to reduced AKT phosphorylation. Interestingly, immunofluorescence analysis evidenced that endometrioid adenocarcinoma tissues displayed, similarly to AN3CA cells, also a GRP78 plasma membrane localization. These data suggest that GRP78 and its plasma membrane localization, might play a role in endometrial cancer development and progression and might constitute a novel target for the treatment of endometrial cancer. J. Cell. Physiol. 229: 1417–1426, 2014. © 2014 Wiley Periodicals, Inc.